2015
DOI: 10.1113/ep085075
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the renal sympathetic nerve and intrarenal angiotensin II modulates proximal tubular sodium reabsorption

Abstract: New Findings r What is the topic of this review?The sympathetic control of renal sodium tubular reabsorption is dependent on activation of the intrarenal renin-angiotensin system and activation of the angiotensin II type 1 (AT 1 ) receptor by angiotensin II. r What advances does it highlight?Despite the fact that the interaction between the sympathetic nervous system and angiotensin II regarding salt reabsorption is a well-known classical mechanism for the maintenance of extracellular volume homeostasis, the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…These data suggest an association between an increased sympathetic tone and NP, however in men the presence of the prostate confounds this association. Similarly, Pontes et al showed how sympathetic overactivity increases renal sodium reabsorption by activation of renin‐angiotensin and Na/H exchanger. More research is needed in this field to reach definitive conclusions.…”
Section: Nocturia Cardiac and Renal Functions: Improve Carementioning
confidence: 91%
“…These data suggest an association between an increased sympathetic tone and NP, however in men the presence of the prostate confounds this association. Similarly, Pontes et al showed how sympathetic overactivity increases renal sodium reabsorption by activation of renin‐angiotensin and Na/H exchanger. More research is needed in this field to reach definitive conclusions.…”
Section: Nocturia Cardiac and Renal Functions: Improve Carementioning
confidence: 91%
“…NHE3 plays a pivotal role in salt and fluid reabsorption in the proximal tubule, and is required for ANG II-induced hypertension in mice (580). It should also be noted that renal sympathetic nerve stimulation leads to NHE3-dependent proximal tubule sodium reabsorption via enhanced generation of intrarenal ANG II (831,832). ANG II activates NHE3 via Ca 2ϩ , calmodulin (CaM), and CaMKII.…”
Section: Salt and Water Balancementioning
confidence: 99%
“…Moreover, these results suggest, that intrarenal mechanisms that regulate the differential expression of Ang II and ACE2 exacerbated by a high-sodium diet, would not be a dependent mechanism of oxidative stress. In this sense it has been shown that in physiological conditions, acute renal sympathetic nerve activity modulates sodium reabsorption by increasing intrarenal Ang II generation and activation of the luminal membrane AT1R[44]. It has been recently shown that activation of renal nervous system results in higher levels of intrarenal angiotensinogen and Ang II independent of changes in renal function and systemic RAS[45].…”
Section: Discussionmentioning
confidence: 99%